Thyroxine Supplementation in Pregnant Women After Thyroidectomy for Thyroid Cancer and Neonatal Birth Weight - Ding, Zheng; Guo, Fei; Zhou, Yulai; Huang, Xiaoyi; Liu, Zhiwei; Fan, Jianxia (Frontiers in Endocrinology, 2021)
Patients are often supplemented with a sufficient dose of thyroxine after thyroidectomy for thyroid cancer. However, the influence of thyroxine supplementation on fetal growth in pregnant women after thyroidectomy for thyroid cancer remains unclear. The aim of this study was to investigate the effect of thyroxine supplementation on neonatal birth weight. This cohort study included 49,896 pregnant women (278 patients with a history of thyroidectomy for thyroid cancer and 39,363 control cases after exclusion). Thyroid parameters were examined in pregnant women and their newborns. The associations between maternal thyroid function and neonatal birth weight and small for gestational age were studied using regression analyses. In the levothyroxine supplementation group, free thyroxine (FT4) levels were significantly higher in both early pregnancy (P < 0.001) and late pregnancy (P < 0.001) groups than in the control group. Furthermore, levels of neonatal thyroid stimulating hormone (P = 0.032) and birth weight (P = 0.043) were significantly lower than those in the control group. We also observed a significant inverse association between maternal FT4 levels in early pregnancy and neonatal birth weight (P=0.028), especially in male newborns (P=0.036). In summary, after thyroidectomy for thyroid cancer, a sufficient dose of thyroxine supplementation in early pregnancy is significantly associated with reduced birth weight and may need to be monitored.